Effects of pectin on fermentation characteristics, carbohydrate utilization, and microbial community composition in the gastrointestinal tract of weaning pigs. Issue 1 (20th June 2016) - Tian, Lingmin; Bruggeman, Geert; van den Berg, Marco; Borewicz, Klaudyna; Scheurink, Anton J.W.; Bruininx, Erik; de Vos, Paul; Smidt, Hauke; Schols, Henk A.; Gruppen, Harry
Abstract : The effects of three different soluble pectins on the digestion of other consumed carbohydrates, and the consequent alterations of microbiota composition and short chain fatty acids (SCFA) levels in the intestine of pigs is investigated. Low‐methyl esterified pectin significantly decreases the ileal digestibility of starch resulting in more starch fermentation in the proximal colon. Treated soybean meal is mainly fermented in the proximal colon and shifts the fermentation of cereal dietary fiber to more distal parts, resulting in high SCFA levels in the mid colon. The soluble pectins differently affect the digestion processes compared to the control diet and shape the colonic microbiota from a Lactobacillus ‐dominating flora to a Prevotella ‐dominating community, with potential health‐promoting effects. Abstract : Scope: We aimed to investigate the effects of three different soluble pectins on the digestion of other consumed carbohydrates, and the consequent alterations of microbiota composition and SCFA levels in the intestine of pigs. Methods and results: Piglets were fed a low‐methyl esterified pectin enriched diet (LMP), a high‐methyl esterified pectin enriched diet (HMP), a hydrothermal treated soybean meal enriched diet (aSBM) or a control diet (CONT). LMP significantly decreased the ileal digestibility of starch resulting in more starch fermentation in the proximal colon. In the ileum, low‐methyl esterified pectin present was more efficiently fermented by the microbiota than high‐methyl esterified pectin present which was mainly fermented by the microbiota in the proximal colon. Treated soybean meal was mainly fermented in the proximal colon and shifted the fermentation of cereal dietary fiber to more distal parts, resulting in high SCFA levels in the mid colon. LMP, HMP, and aSBM decreased the relative abundance of the genus Lactobacillus and increased that of Prevotella in the colon. Conclusion: The LMP, HMP, and aSBM, differently affected the digestion processes compared to the control diet and shaped the colonic microbiota from a Lactobacillus ‐dominating flora to a Prevotella ‐dominating community, with potential health‐promoting effects.